Almacenamiento masivo de información mediante clúster en el Laboratorio de Redes de la Universidad Técnica de Cotopaxi Extensión La Maná - Garcia Veléz, Walter Elías (2017)
The general purpose of this project is the implementation of a cluster of information storage in networks of the Technical University of Cotopaxi Extension La Maná that will allow to store information, files, programs, which will facilitate its accessibility, reliability and availability. For its realization will use technological resources is going to work with NAS (networked storage server) will also be used software resources in this case will be working with the operating system synology diskstation manager (DSM) this is an operating system based on Explorer that offers tools to access your synology. This server will be installed in the network laboratory of the Technical University of Cotopaxi Extension La Maná and at the same time will be connected the internal network through a network cable, but also will allow access to the server from anywhere in the world using an ip address. Once the cluster is properly configured, this will allow users to be created and provide the necessary permissions such as reading, writing, deleting among others. It will also allow us to create groups where group files can be stored. This cluster will have the advantage that will allow users to access it and share or download files easily from different operating systems as many free as proprietary such as Windows as Mac or Linux, these can be shared from your intranet or through Internet with one of the applications of synology diskstation manager, file station, that allows the users to manage their files in synology NAS easily through a web interface. It will also allow access to files stored on the synology NAS with a mobile device since it has a multiplatform system. This storage cluster will automatically synchronize data from any device when adding a new file or when saving a change the data will be automatically updated on all other devices.